Utilizing the microalgal biomass of Chlorella variabilis and Scenedesmus obliquus produced from the treatment of synthetic dairy wastewater as a biofertilizer. (12th December 2020) - Gatamaneni Loganathan, Bhalamurugan; Orsat, Valerie; Lefsrud, Mark
Abstract: Microalgae are known to have higher growth rates than terrestrial plants and are garnering great attention among researchers as they can produce commodities of high commercial value. Remediating wastewater with microalgae and utilizing it as a biofertilizer could significantly improve the economic standpoint of algal production. In this study, varying concentrations (0%, 40% and 60%) of aqueous cell extracts of Chlorella variabilis and Scenedesmus obliquus cultivated on dairy wastewater were used as a biofertilizer to evaluate plant growth of corn ( Zea mays) and soybean ( Glycine max) up to the mid vegetative stage. The treatments that employed the microalgal consortia as biofertilizer (40% and 60%) exhibited increased growth rates, higher total phenolic content, total flavonoid content, antioxidant activity and minerals when compared to the control group for both corn and soybean.